2010
DOI: 10.1007/s10165-010-0366-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of tocilizumab in rheumatoid arthritis patients seen in daily clinical practice in Japan: results from a retrospective study (REACTION study)

Abstract: Tocilizumab, a humanized monoclonal antibody to the interleukin 6 (IL-6) receptor, was approved for use as rheumatoid arthritis (RA) therapy in Japan in 2008, but its efficacy and tolerability in daily practice has not yet been reported. We report the results of a multicenter retrospective study on the efficacy and safety of tocilizumab involving all patients (n = 229) who were started on tocilizumab therapy at three rheumatology institutes in Japan from April 2008 through to March 2009. Tocilizumab was infuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 35 publications
4
23
1
1
Order By: Relevance
“…The overall retention rate observed in the present study (82.4% at 26 weeks and 69.7% at 52 weeks) falls within the range reported for infliximab (75.6% at 54 weeks) [15], etanercept (85.1% at 6 months) [17], and tocilizumab (79.5% at 24 weeks) [28] in daily clinical practice. However, it is not surprising that the retention rate varies among different biologics, as it is believed to be influenced by numerous factors other than efficacy and safety, such as co-morbidity, concomitant therapy, costs, launch timing, and availability of other therapies [29].…”
Section: Discussionsupporting
confidence: 85%
“…The overall retention rate observed in the present study (82.4% at 26 weeks and 69.7% at 52 weeks) falls within the range reported for infliximab (75.6% at 54 weeks) [15], etanercept (85.1% at 6 months) [17], and tocilizumab (79.5% at 24 weeks) [28] in daily clinical practice. However, it is not surprising that the retention rate varies among different biologics, as it is believed to be influenced by numerous factors other than efficacy and safety, such as co-morbidity, concomitant therapy, costs, launch timing, and availability of other therapies [29].…”
Section: Discussionsupporting
confidence: 85%
“…Frequencies of 22.8–49.2% for clinical remission (DAS28 < 2.6) at week 24, determined in almost all of the mentioned studies, also appear to be less than the 71.4% observed in the present study (with 76.2% as the final cumulative frequency).…”
Section: Discussioncontrasting
confidence: 64%
“…Most of the reference studies reported −2.5 to −3.3 difference between the baseline and the last (week 24) mean DAS28, not far from −3.3 obtained in our study, but with a slower decrement rate . Relatively the same is true for the mean HAQ score, with a similar rate of decrement observed with a lower baseline value (1.1) compared to the references (1.5–1.6).…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have shown that a frequent reason for the discontinuation of biological agents is the development of AE 57 1316. Mid to long-term tolerability of TNF inhibitors6 13 14 1624 and tocilizumab7 15 25 has been reported, and some studies have directly compared drug retention rates among TNF inhibitors or between TNF inhibitors and other biological agents 14 16 17 2527. To summarise, infliximab had the lowest overall retention rate among infliximab, etanercept and adalimumab14 16 17 and among infliximab, etanercept and anakinra 26.…”
mentioning
confidence: 99%